0
$\begingroup$

Let $X$ be the set of all relations over $\mathbb N$. Let $R\in X$. Let $r(R)$ be the reflexive closure of some relation $R$. Accordingly, let $s(R)$ be the symmetric closure of $R$. I need to prove that $s(r(R))=r(s(R))$.

While this totally makes sense, I'm not sure how to formally prove this.

For any $(a,b)\in R$ such that $a\neq b$ we have that $r(R)=\{(a,b)\}\cup \{(a,a), (b,b)\}$. If $(a,a)\in R$ then $r(R)=R$. So essentially $r(R)$ is a union of all original pairs in $R$ plus their reflexive "counterparts". Applying $s$ onto $r(R)$ will add symmetric "counterparts" for all pairs $(a,b)$ such that $a\neq b$ while the pairs of type $(a,a)$ are already symmetric. So all pairs $(a,a)\in R$ are already symmetric and reflexive therefore applying $s$ and $r$ on them will just return the pairs themselves, while applying $r$ and $s$ on all pairs $(a,b)$ will result in the union of symmetric and reflexive pairs which is the same for $s(r(R))=r(s(R))$.

| cite | improve this question | | | | |
$\endgroup$
0
$\begingroup$

R' = { (a,b) : bRa }. sR = R $\cup$ R'. rR = R $\cup$ N×N.
rsR = sR $\cup$ N×N = R $\cup$ R' $\cup$ N×N.
srR = s(R $\cup$ N×N) = R $\cup$ N×N $\cup$ (R $\cup$ N×N)'
. . = R $\cup$ N×N $\cup$ R' $\cup$ N×N.

| cite | improve this answer | | | | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.